The Choice of the Type of Anesthesia for Carotid Endarterectomy (Review) - Oleg V. Simonov; Igor N. Tyurin; Alexander D. Pryamikov; Alexey B. Mironkov (Общая реаниматология, 2018)
The article summarizes the international experience of using different types of anesthesia for the surgical treatment of carotid artery lesions. The anesthesiology support of surgery on the carotid basin includes general and combined anesthesia of various types. The regional anesthesia is a separate field in the carotid surgery. The paper presents the advantages and disadvantages of each anesthetic technique. The recent publications show the superiority of regional anesthesia in terms of its cost-effectiveness, less frequent use of temporary intraluminal shunt, the possibility to constant monitoring of patient’s neurological status throughout the operation, and lower incidence of neurologic and cardiac complications. Complications of the regional anesthesia and the methods of their correction are described in detail. There is still no consensus about the choice of the optimal type of anesthesia for carotid endarterectomy, hence further large-scale randomized trials are needed.